Energy efficient optimal sink position selection algorithm for wireless sensor networks - TANG Wei; GUO Wei (Tongxin xuebao)
The selection of sink position and the routing optimization for energy efficiency were combined,and the shortest path tree（SPT） tessellation was defined.The structure of the SPT tessellation cells in 2-dimension space was analyzed,and a method to search neighboring cells was presented.Three heuristic algorithms were also designed.Simu-lation experiments are conducted to analyze and compare the performance of the proposed algorithms,and the results show that the performance of the algorithms is close to or able to converge to the global optimality.